2018
DOI: 10.1111/eva.12642
|View full text |Cite
|
Sign up to set email alerts
|

Measures of effective population size in sea otters reveal special considerations for wide‐ranging species

Abstract: Conservation genetic techniques and considerations of the evolutionary potential of a species are increasingly being applied to species conservation. For example, effective population size (N e) estimates are useful for determining the conservation status of species, yet accurate estimates of current N e remain difficult to obtain. The effective population size can contribute to setting federal delisting criteria, as was done for the southern sea otter (Enhydra lutris nereis). After being hunted to near extinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 75 publications
3
21
0
Order By: Relevance
“…, Gagne et al. ). Therefore, we examined harvest patterns and potential impacts of harvest at both the stock and subregional scales.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…, Gagne et al. ). Therefore, we examined harvest patterns and potential impacts of harvest at both the stock and subregional scales.…”
Section: Methodsmentioning
confidence: 99%
“…Harvest occurs throughout most of this region with the exception of Glacier Bay National Park, ❖ www.esajournals.org where U.S. National Park Service regulations prohibit it. While the USFWS manages sea otters at the stock level, a number of recent studies and reviews have highlighted that demographically important processes in sea otter populations, including density-dependent resource limitation, occur at much smaller scales because of the low mobility and high site fidelity of mature sea otters (Bodkin 2015, Tinker 2015, Tinker et al 2017, Gagne et al 2018. Therefore, we examined harvest patterns and potential impacts of harvest at both the stock and subregional scales.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The sea otter population is not spatially homogeneous, but densest at the range center on the Monterey Peninsula (Nicholson et al, ). There it is either approaching, or already at, carrying capacity (Gagne et al, ; Smith, Newsome, Estes, & Tinker, ). As a result, any appreciable and sustained population growth must come from the range peripheries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous samples were collected from widely dispersed locations and shared among studies, and they suggested that sampling on a microgeographic scale should be considered in future genetic analysis. More recent highresolution sampling of the southern sea otter population in California did find evidence for isolation by distance and cryptic genetic structure with implications for estimates of effective population size (Gagne et al, 2018). From a conservation genetics perspective, it is interesting to note that genetic diversity is highest in translocated populations derived from two source populations (Larson et al, 2002b).…”
Section: Key Questions and Challenges For Future Research And Managementmentioning
confidence: 99%